2012
DOI: 10.1186/1756-3305-5-249
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for genetic differentiation at the microgeographic scale in Phlebotomus papatasi populations from Sudan

Abstract: BackgroundCutaneous Leishmaniasis (CL) is endemic in Sudan. It is caused by Leishmania major parasites and transmitted by Phlebotomus papatasi sandflies. Recently, uncommon clinical manifestations of CL have been reported. Moreover, L. donovani parasites that cause Visceral Leishmaniasis (VL) have been isolated from CL lesions of some patients who contracted the disease in Khartoum State, Central Sudan with no history of travelling to VL endemic sites on south-eastern Sudan. Because different clinical manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…-Algeria (Bounamous et al, 2008Depaquit et al, 2008bDepaquit et al, , 2013Depaquit et al, , 2014Franco et al, 2010), -Benin , -Burkina Faso: (Depaquit et al, 2005a(Depaquit et al, , 2008b, -Cameroon , -the Comoros (Randrianambinintsoa et al, 2012), -Egypt (Booth et al, 1991;Esseghir et al, 1997;Depaquit et al, 2000Depaquit et al, , 2008bDepaquit et al, , 2014Esseghir and Ready, 2000;Elnaiem et al, 2005;Hamarsheh et al, 2007;Khalid et al, 2012;Minter et al, 2013), -Ethiopia (Esseghir et al, 1997;Esseghir and Ready, 2000;Seblova et al, 2013), -the Republic of Guinea , -Kenya (Mukhopadhyay et al, 2000;Esseghir et al, 1997;Depaquit et al, 1998Depaquit et al, , 2000Depaquit et al, , 2008bEsseghir and Ready, 2000), -Madagascar (Depaquit et al, 2004a(Depaquit et al, ,b, 2007(Depaquit et al, , 2008aRandrianambinintsoa et al, 2012, -Mali (Khalid et al, 2010), -Morocco (Esseghir et al, 1997;Di Muccio et al, 2000;Pesson et al, 2004;Yahia et al, 2004;Hamarsheh et al, 2007;Moin-Vaziri et al, 2007a;Baron et al, 2008;Franco et al, 2010;…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…-Algeria (Bounamous et al, 2008Depaquit et al, 2008bDepaquit et al, , 2013Depaquit et al, , 2014Franco et al, 2010), -Benin , -Burkina Faso: (Depaquit et al, 2005a(Depaquit et al, , 2008b, -Cameroon , -the Comoros (Randrianambinintsoa et al, 2012), -Egypt (Booth et al, 1991;Esseghir et al, 1997;Depaquit et al, 2000Depaquit et al, , 2008bDepaquit et al, , 2014Esseghir and Ready, 2000;Elnaiem et al, 2005;Hamarsheh et al, 2007;Khalid et al, 2012;Minter et al, 2013), -Ethiopia (Esseghir et al, 1997;Esseghir and Ready, 2000;Seblova et al, 2013), -the Republic of Guinea , -Kenya (Mukhopadhyay et al, 2000;Esseghir et al, 1997;Depaquit et al, 1998Depaquit et al, , 2000Depaquit et al, , 2008bEsseghir and Ready, 2000), -Madagascar (Depaquit et al, 2004a(Depaquit et al, ,b, 2007(Depaquit et al, , 2008aRandrianambinintsoa et al, 2012, -Mali (Khalid et al, 2010), -Morocco (Esseghir et al, 1997;Di Muccio et al, 2000;Pesson et al, 2004;Yahia et al, 2004;Hamarsheh et al, 2007;Moin-Vaziri et al, 2007a;Baron et al, 2008;Franco et al, 2010;…”
Section: Resultsmentioning
confidence: 97%
“…A few studies have been carried out on microsatellites Watts et al, 2005;Zhang et al, 2009Zhang et al, , 2013Mahamdallie et al, 2010;Khalid et al, 2012;Santos et al, 2013) and the majority of studies focuses on the amplification of one or several molecular markers.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies have demonstrated the presence of genetically different populations of P. papatasi in Sudan [43] that could be able to transmit different strain/hybrids. Moreover, high polymorphism has been attributed to L. major causing cutaneous diseases in Iran [44].…”
Section: Discussionmentioning
confidence: 99%